Transparent near-infrared perovskite light-emitting diodes - Chenchao Xie (Nature Portfolio, 2020)
Xie et al. report a transparent near-infrared light-emitting diode based on semiconducting lead halide perovskite. This technology could enable security and sensing features on space constrained smart-watches, phones, gaming consoles and augmented or virtual reality headsets.